THE INFLUENCE OF INTELLECTUAL CAPITAL ON ENTERPRENEURIAL PERFORMANCE (CLUSTER ANALYSIS SCENARIO) - Petković, Ivana (Economic Outlook, 2023)
The main motive of this research is to determine the impact that intellectual capital has on entrepreneurial performance. The change in the performance of human capital as an indicator formed by the World Bank was used as a basis in order to define possible progress or stagnation in the development of intellectual capital in the countries of the European Union (including Great Britain) in comparison with Serbia. Namely, the human capital index as an integral part of intellectual capital will be analyzed using cluster analysis based on Ward’s method, in order to determine groups of countries that are similar to each other in the development of intellectual capital. The reference years for the analysis of data from the Eurostat database are 2018 and 2020. The change in the value of the human capital index in the mentioned years should show the migration of countries from one cluster to another due to the improvement/deterioration of intellectual capital performance. The output results of the cluster analysis show the formation of five clusters of countries. In 2020, Serbia recorded a decline in the human capital index and thus positioned itself in Cluster 5, which in terms of performance lags behind the cluster of countries that are leaders in this segment.